VERTICAL GRAIN-SIZE VARIABILITY WITHIN A TURBIDITE LEVEE: AUTOCYCLICITY OR ALLOCYCLICITY? A CASE STUDY FROM THE RHôNE NEOFAN, GULF OF LIONS, WESTERN MEDITERRANEAN - Dennielou B.; Huchon A.; Berné S.; Beaudouin C. (My University, 2006)
The fining upward trend commonly described on levees of turbidite systems can be either attributed to changes in the sediment supply (external forcing = allocyclic) or changes in the spillover processes related to the growth of the levee (internal forcing = autocyclic). However the real causes remain speculative and difficult to demonstrate. Knowledge of vertical change in flow velocity (or grain size) in turbidity currents, of the turbidity current's height, as well as the growth rate of a levee are theoretically sufficient to describe the evolution of the grain size of a leveed turbidite sequence deposited by spillover processes. A piston core (MD99-2344) retrieved on the right levee of the Petit-Rhône neofan, sampled an 8.50 m long turbidite sequence containing more than one hundred turbidite beds and showing a marked fining upward trend. With the help of two profiles describing respectively the vertical velocity [Stacey, M. and Bowen, A.J., 1988b. The vertical structure of turbidity currents and a necessary condition for self-maintenance, Journal of Geophysical Research, pp. 3543-3553.] and the vertical grain size [Migeon, S., 2000. Dunes géantes et levées sédimentaires en domaine marin profond: approche morphologique, sismique et sédimentologique. PhD Thesis, Université Bordeaux 1, Talence, France, 288 pp.] of a turbidity current, and a simple graphical method, we test several hypotheses on the height of the turbidity current and on the grain size at the bottom of the turbidity current and we attempt to reproduce the vertical fining upward trend. Our results show that the fining upward trend of the turbidite facies can be explained by the aggradation of the turbidite levee and the gradual confinement of the turbidity currents in the channel. This is, therefore, an autocyclical phenomenon. However a high frequency variability of the grain size overprinted on the trend cannot be explained by internal forcing and is believed to be allocyclical, depending on changes to the sediment input. The vertical grain-size profile allows more realistic flow conditions to be determined and shows that the vertical velocity profile does not describe the ability of turbidity current to transport sediment. This simple graphical method allows a better understanding and quantification of the forcing on turbidite deposits and improves description of the characteristics of the turbidity currents from the grain size of the deposits. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALLOCYCLICITY; AUTOCYCLICITY; CHANNEL-LEVEE; GRAIN SIZE; TURBIDITE